SYNTHESIS AND ANTIPLASMODIAL ACTIVITY TESTING OF (1)-N-(4-METHOXYBENZYL)-1,10-PHENANTHROLINIUM BROMIDE - Ruslin Hadanu; Sabirin Mastjeh; Jumina Jumina; Mustofa Mustofa; Mahardika Agus Widjayanti; Eti Nurwening Sholikhah (Universitas Gadjah Mada, 2007)
Synthesis of (1)-N-(4-methoxybenzyl)-1,10-phenanthroline bromide from 1,10-phenanthroline monohydrate and 4-methoxybenzaldehyde as starting material and evaluation of its antiplasmodial activities have been carried out. The 4-methoxybenzyl alcohol was prepared from 4-methoxy-benzaldehyde using sodium borohydride (NaBH4) reagent and ethanol absolute solution. The mixture was refluxed for 3 h. To yield colorless dilution compound with 90.41 % in efficiency. Furthermore, bromination of 4-methoxybenzyl alcohol with phosphorus bromide (PBr3) was conducted by refluxing for 3 h. The product of this reaction was yellow liquid of 4-methoxybenzyl bromide, 79.03% yield and 95.34 % purity. The final step of reaction was benzylation of 1,10-phenanthroline monohydrate with 4-methoxybenzyl bromide reagent. It was conducted by refluxing in aceton for 8 h at 55 oC. The yield of the reaction was (1)-N-(4-methoxybenzyl)-1,10-phenanthroline bromide (77.63%). It is pink solid form, and its melting point is 192-193 oC. Identification of the product was carried out by means of GC-MS, IR and 1H-NMR spectrometers. The in vitro antiplasmodial activity on chloroquine-resistant Plasmodium falciparum FCR-3 strain and chloroquine sensitive P. falciparum D10 strain for (1)-N-(4-methoxybenzyl)-1,10-phenanthroline bromide were determined by microscopic method. The result showed that after 72 h incubation, it has IC50 0.93±0.02 µM and 1.21±0.09 µM, respectively.